2012
DOI: 10.1177/1359104512448146
|View full text |Cite
|
Sign up to set email alerts
|

“That must be so hard”- Examining the impact of children’s palliative care services on the psychological well-being of parents

Abstract: In 2003 the New Opportunities Fund (NOF, now known as The Big Lottery) awarded £48 million to 70 home-based care teams to enable them to provide a range of services to allow children with non-malignant life-limiting conditions to be cared for at home. Four grants were made available in Bristol, North Somerset, South Gloucestershire and Bath and North East Somerset to enhance existing children's palliative care services. As there is limited evidence about the impact of palliative care services on psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 6 publications
0
24
0
10
Order By: Relevance
“…14 Similarly, a 12-month follow-up of UK parents of children with life-threatening conditions showed no change in stress and psychological well-being from the time of referral to home-based palliative care services. 15 The impact of respite on the well-being of caregivers of children with life-threatening conditions therefore remains unclear. The available research is mostly qualitative, with few longitudinal designs and quantitative assessments.…”
Section: A Pre-test and Post-test Study Of The Physical And Psychologmentioning
confidence: 99%
“…14 Similarly, a 12-month follow-up of UK parents of children with life-threatening conditions showed no change in stress and psychological well-being from the time of referral to home-based palliative care services. 15 The impact of respite on the well-being of caregivers of children with life-threatening conditions therefore remains unclear. The available research is mostly qualitative, with few longitudinal designs and quantitative assessments.…”
Section: A Pre-test and Post-test Study Of The Physical And Psychologmentioning
confidence: 99%
“…Because a lack of social support has been associated with higher levels of distress, psychological morbidity, and post-traumatic stress disorder (PTSD) [ 108 , 109 ], and because increased community and peer social support have been shown to ameliorate distress in parents, it may be beneficial for PPC practitioners to facilitate channels of personal and systems engagement between parents of ill children and community organizations or peer support [ 108 ].…”
Section: What Providers Can Domentioning
confidence: 99%
“…These activities allow caregivers to nurture and sustain relationships, while reducing threat and defensiveness in stressful times [ 112 ]. Because of pre-existing socio-ecological issues, PPC services alone may be unable to address the social and emotional needs of parents [ 108 ]. However, it has been suggested that it is not necessarily an “intervention” that decreases distress for caregivers, but the practice of good pediatric palliative care that includes the previously-mentioned treatment of symptoms (in the patient), good communication, care coordination, and decision-making support that affect psychological outcomes for parents in PPC settings [ 108 ].…”
Section: What Providers Can Domentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, previous studies of Ryff, 2014;Srimathi and Kiran Kumar, 2010;Ryff and Heidrich;1997;Haris, Martin, and Martin, 2013) revealed that during the courses, female were better prepared in achieving better well-being. In contrary, male had better well-being because they interacted more and had better social support (Gupta and Prescott, 2012). In contrary, male pre-service teachers aged 17-19 years old were unlikely to contemplate about their career in the future after graduating.…”
Section: Preservice Teachers' Psychological Well-being Profilementioning
confidence: 94%